The Land of the Blue Flower - Burnett, Frances Hodgson, 1849-1924 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Land of the Blue Flower" by Frances Hodgson Burnett is a novel written in the early 20th century. The story unfolds in a fantastical kingdom, initially known as King Mordreth's Land, which is transformed through the reign of the kind and wise King Amor. The book explores themes of beauty, kindness, and the power of positive thoughts and actions, all set against a backdrop of nature and magic. The narrative follows the journey of King Amor, who was nurtured by the Ancient One on a mountain crag, away from the negativity and strife of the kingdom below. As he grows, Amor learns to appreciate the wonders of the sun, the storm, and the stars, which shape his benevolent character. When he ascends to the throne, he introduces the Law of the Blue Flower, mandating that every person plant and care for this special flower, symbolizing hope and unity. The act promotes harmony among the people, leading to the reclamation of their land from misery to beauty, as they work together and embrace positivity. Ultimately, King Amor demonstrates that love and beauty can triumph over darkness, transforming his realm into a joyful and vibrant land. (This is an automatically generated summary.)
Release date is 2004-03-01
Produced by Juliet Sutherland, Charles Franks and the Online Distributed Proofreading Team
Keywords: Fairy tales